DIGITAL COMIC: AN INNOVATION OF USING TOONDOO AS MEDIA TECHNOLOGY FOR TEACHING ENGLISH SHORT STORY - Asri Siti Fatimah; Santiana Santiana; Yuyus Saputra (University of Kuningan, 2019)
This study investigates the use of ToonDoo as media technology for teaching English short story. ToonDoo as the newest technology for creating comic or picture story is very beneficial helping teacher to creatively provide innovative strategy providing better classroom environment for the English learners, especially for those studying English short story. As the invented prose narrative shorter than a novel dealing with a few characters, short story can give an important content raising cultural awareness, linguistic awareness, motivation, and is claimed to improve all four skills. Therefore, this study aims at knowing how the implementation of ToonDoo in teaching English short story and finding out the benefits of this tool for teaching performance. To gain the data, reflective journal created by a pre-service teacher who becomes the participant of the study and interview were used to reflect the process of creating Toondoo and the process of teaching English short story using this tool. The findings showed that this tool can be used to promote students’ speaking skill. Toondoo is very helpful to facilitate students’ imagination promoting their speaking ability, producing better learning experience, and creating a good classroom atmosphere.